2009
DOI: 10.5835/jecm.omu.26.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intrauterine Acute Ethanol Exposure on Developing Sciatic Nerves and Their Myelination: A Stereological Study

Abstract: Ethanol (ETH) delays myelination in the sciatic nerve of rat following fetal exposure. It has been suggested that melatonin (MLT), a naturally occurring indole, may be a potential protective agent for ETH toxicity, possibly due to its protective effects against free radical damage in experimental models. However, the precise mechanism of MLT protection in the development of the rat sciatic nerves and their myelination is unclear. In this study, the effect of ETH, MLT and ETH+MLT on the myelin thickness, axon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The findings from a previous study suggested that melatonin could suppress collagen scar formation after PNI ( 23 ). Melatonin also increased the number of axons and the thickness of the myelin sheath after PNI ( 4 ). Stavisky et al ( 25 ) demonstrated that melatonin enhanced the repair of sciatic nerve crush injuries in rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings from a previous study suggested that melatonin could suppress collagen scar formation after PNI ( 23 ). Melatonin also increased the number of axons and the thickness of the myelin sheath after PNI ( 4 ). Stavisky et al ( 25 ) demonstrated that melatonin enhanced the repair of sciatic nerve crush injuries in rats.…”
Section: Discussionmentioning
confidence: 97%
“…After an injury, peripheral axons activate the intrinsic growth capacity in the neuronal cell body and promote axonal regeneration ( 2 ). Previous studies have suggested that Schwann cells are important in the regeneration of peripheral axons and functional recovery ( 3 , 4 ). After the events of a PNI, mature Schwann cells dedifferentiate into progenitor-like Schwann cells, known as Schwann cell precursors, promote myelin debris clearance and tubular reconstruction, and also form a cellular bridge spanning the gap between ends of damaged nerves ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the therapeutic use of MLT could be a promising strategy to counteract PNI-induced neuronal disability. It has been defined that MLT has positive effects on axon number and myelin sheath thickness by preventing collagen deposition and neuroma formation after traumatic events in peripheral nerves (Aktas¸ et al, 2009). Degeneration of the endoneural and perineural sheath, hyperplasia of schwannocytus, and degeneration of axonal structures were observed in the defect group.…”
Section: Discussionmentioning
confidence: 99%
“…41 Data from the literature, together with our studies using a different kind of experimental injury model, showed that MLT has positive effects on the number of axons and the thickness of the myelin sheath by inhibiting collagen accumulation and neuroma formation following traumatic events to peripheral nerves, and on the myelination of a developing peripheral nerve after intrauterine ethanol exposure. 42 As a result, the minimal dose of MLT necessary for an effect on peripheral nerve regeneration can be ascertained. Ulugol et al determined the effects of intracerebroventricular (i.c.v.)…”
Section: Free Radical Scavenging Effects Of Melatonin In Peripheral Nmentioning
confidence: 99%